Multibeam bathymetry processed data (Kongsberg EM 122 working area dataset) of RV SONNE during cruise SO268/3, North Pacific Ocean - Tanja Dufek; Cara Schniotalla; Stefan Kinne; Harald Sternberg (PANGAEA, 2023)
The multibeam echo sounder (MBES) data was collected from the 31.05.2019 (16:07 UTC) when leaving the Canadian EEZ to the 25.06.2019 (08:08 UTC) before entering the Japanese EEZ with the Kongsberg EM122 on RV SONNE in the North Pacific Ocean (SO268/3). The data collected in the Hawaiian (14.06.2019 08:56 UTC - 16.06.2019 18:50) and Japanese EEZ (23.06.2019 05:59 -24.06.2019 21:38 UTC) is not part of this data delivery. The deep-water MBES EM122 operates with an acoustic frequency of 12 kHz and a beam opening angle of 0.5° x 1°. The time, motion and position data (WGS84, geographic) was measured by the Kongsberg Seapath system on board. During the acquisition the echo sounder was monitored as well as settings and filter adjusted according to the environment. The transit speed was up to 13 knots. The swath opening angle was set between 60° and 65° resulting in a swath width of about 22 km in 5,000 m water depth. The ping mode was set to Auto, which enabled the system to use continuous wave pulses in shallow modes and frequency modulated pulses in deep modes. Further, high density and dual swath mode were continuously applied. As the data was collected during transit, no specific surveys were performed. During the cruise, eight sound velocity profiles (SVP) were derived from CTD (conductivity, temperature, depth) measurements and applied in the MBES acquisition software SIS to ensure correct depth measurements. Before the first SVP as taken, a synthetic SVP extracted from the Qoeld Ocean Atlas 2009 from NOAA (Levitus, 2013) using the software "Sound Speed Manager" (developed by the UNH Center for Coastal and Ocean Mapping and NOAA Coast Survey Development Laboratory (CSDL)) was applied. The SVP data is not part of this submission. The data was post-processed using the software QPS Qimera. No further SVP re-computation, navigation correction or tide correction was applied. Erroneous depth measurements were deleted manually by using the swath and slice editor. The vertical datum is mean sea level (MSL). The cleaned data was exported as bathymetric grids in a resolution of 60 m (geotiff format, WGS84 (EPSG:4326)).